Pemahaman Pengakuan Pendapatan atas Transaksi Jual Beli Hasil Bumi pada Usaha Sejati - Alfila, Theresia; Indrawati, Eka; Agnesia , Cheny; Mitan , Virginia Martha (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
This community service aims to understand the sale and purchase of agricultural products in a true business. Where the management of agricultural products can improve people's standard of living, by knowing the application of sales and purchase reports. It is hoped that this PkM activity can support genuine businesses in achieving sales and purchase targets for agricultural products. In achieving good targets, a true business must implement good sales and purchasing report presentation. The method used in this PkM is skills training regarding sales and purchase reports of agricultural products in the form of manual recording and is carried out in 2 days with the activity participants being true business managers in the field of buying and selling agricultural products. The results obtained from this activity are the application of income recognition for sales and purchase transactions of agricultural products in real businesses.